PERSONALITY TYPES OF LITHUANIAN INDIVIDUAL INVESTORS - Jureviciene, Daiva; Novickyte, Lina; Dubinskas, Pertas; Keliuotyte, Greta (European Scientific Journal, ESJ, 2013)
Scientists explore investors’ behaviour in financial markets for more than a century. Studies conducted agree that financial behaviour is the intersection of economics, psychology and sociology. Studies of investors’ behaviour are important both to scientists and financial intermediaries, because investors‘ decisions influence not only well-being of themselves, but also the dynamics of financial market. In this paper recent researches in the field of behavioural finance are systematized. Based on M. M. Pompian methodology (2006) the study of Lithuanian individuals was conducted. The aim of this study was to determine personality types of investors. Research results showed that investors in Lithuania are rather thoughtful, but only six personality types (M. Pompian determines eight types) have been distinguished. It was found that Pragmatist Integrator Reflector, Pragmatist Framer Realist and Idealist Integrator Realist investors’ types dominate in Lithuania.